Analisis Kecenderungan Gaya Kepemimpinan Kepala Sekolah Dasar Islam Nahdlatul Ulama Pare Dalam Perspektif Teori Gaya Kepemimpinan Tiga Dimensi Wiliam James Reddin - Turmudi, Imam (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This article examines how the leadership style trend of the head of the Islamic Elementary School Nahdlatul Ulama Pare in the perspective of Williams James Reddin's three-dimensional theory. The principal should apply an effective leadership style. Among the figures who created the theory of effective leadership style is William James Redin in the theory of three-dimensional leadership. This leadership style theory will be the analytical knife of researchers in analyzing the trend of leadership style at the Nahdlatul Ulama Islamic Elementary School (SDI NU) Pare. SDI NU Pare is one of the most advanced and successful schools because apart from being accredited A, this school has achieved various achievements in both academic and non-academic fields. The progress and achievements of SDI NU Pare cannot be separated from the success of the principal in leading the institution. Therefore, the researcher is interested in analyzing the trend of leadership style used by the principal of SDI NU Pare and what policies are applied to become an advanced and high-achieving school. The method used in this research is descriptive qualitative with the results describing the trend of the leadership style of the SDI NU Pare principal and the policies applied so that the school is advanced and has achievements.